Improvement in corrosion resistance of magnesium-aluminum alloy via friction stir processing - Dani, Minal S.; Dave, I.B.; Joseph, Alphonsa (Penerbit Universiti Kebangsaan Malaysia, 2021)
Friction stir processing was done for surface modification of cast Magnesium-Aluminum alloy. The microstructural characteristics related to different phases of untreated cast Magnesium-Aluminum alloy, friction stir processed under different process parameters like rotational speeds at 380rpm and 545 rpm with 31.5 mm/min transverse speed with and without pure aluminum powder were investigated by Metallurgical microscopy at lower magnification and scanning electron microscopy at higher magnification. Pure aluminum powder of fine size (~19μm) was filled in the groove made at the center of the Magnesium-Aluminum alloy plate which cover 33 vol% of pure aluminum during friction stir processing. The electrochemical behavior of the Magnesium-Aluminum alloy, Friction stir processed Magnesium-Aluminum alloy without aluminum powder and Friction stir processed Magnesium-Aluminum alloy with pure aluminum powder were investigated using Potentiostat in 5 wt % sodium chloride (NaCl) solution.Surface of all conditions specimens were analyzed for the phases present on the surface by X-Ray Diffractometer (XRD) which revealed different peaks of α-Mg phase, β-phases (Mg17Al12) and Pure Aluminum . In friction stir processed Magnesium-Aluminum alloy double pass with aluminum powder all these peaks were observed. The electrochemical corrosion tests revealed the least corrosion rate (0.603 X 102mpy) for friction stir processed double pass with aluminum powder amongst all the tested specimens. The improvement in corrosion resistance of friction stir processed double pass with aluminum powder is because of more formations of the β-phases (Mg17Al12) and aluminum dissolved in the α-Mg phase.